2013
DOI: 10.1113/jphysiol.2013.254144
|View full text |Cite
|
Sign up to set email alerts
|

Apelin acts in the subfornical organ to influence neuronal excitability and cardiovascular function

Abstract: Key points• Apelin receptor mRNA is expressed in the subfornical organ.• Apelin influences the excitability of the majority of subfornical organ neurons, with similar proportion showing depolarizing and hyperpolarizing effects.• Hyperpolarizations appear to result from the activation of a sustained voltage-activated potassium conductance, while depolarizations may result from modulation of a non-selective cationic conductance.• In vivo microinjection of apelin into the subfornical organ results in decreases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 57 publications
(82 reference statements)
3
29
1
Order By: Relevance
“…Similarly, studies of peripheral apelin administration in conscious rats have reported both increases and decreases in MABP (Cheng et al 2003;Kagiyama et al 2005). These are ambiguous results in comparison to the MABP decreases consistently observed in anesthetized rats (Cheng et al 2003;Dai et al 2013;Lee et al 2000;Lee et al 2005;Reaux et al 2001;Tatemoto et al 2001). Interestingly, and perhaps of relevance to the different responses reported in rats, a study in sheep given a large systemic dose of apelin-13 led to a biphasic response in blood pressure (BP), with an initial transient decrease in BP immediately giving way to an increase in BP.…”
Section: The Ar In the Cardiovascular Systemcontrasting
confidence: 41%
See 1 more Smart Citation
“…Similarly, studies of peripheral apelin administration in conscious rats have reported both increases and decreases in MABP (Cheng et al 2003;Kagiyama et al 2005). These are ambiguous results in comparison to the MABP decreases consistently observed in anesthetized rats (Cheng et al 2003;Dai et al 2013;Lee et al 2000;Lee et al 2005;Reaux et al 2001;Tatemoto et al 2001). Interestingly, and perhaps of relevance to the different responses reported in rats, a study in sheep given a large systemic dose of apelin-13 led to a biphasic response in blood pressure (BP), with an initial transient decrease in BP immediately giving way to an increase in BP.…”
Section: The Ar In the Cardiovascular Systemcontrasting
confidence: 41%
“…Microinjection of apelin into the RVLM caused chronic increases in mean arterial blood pressure (MABP) and cardiac hypertrophy. In contrast to these CNS effects, peripherally administered apelin has typically been shown to decrease MABP (Cheng et al 2003;Dai et al 2013;Lee et al 2000;Lee et al 2005;Reaux et al 2001;Tatemoto et al 2001). Interestingly, this effect is fully blocked by the C-terminally modified apelin-13 analogue F13A, which acts as an antagonist at the AR, preventing the typical apelin-induced MABP reduction (Lee et al 2005).…”
Section: The Ar In the Cardiovascular Systemmentioning
confidence: 96%
“…ACE2 hydrolyses apelin or AngII with similar catalytic efficiency [77]. Intracerebroventricular administration of apelin does not modify BP [78], but its administration into the SFO decreases BP and heart rate as a consequence of its modulating effects on neuron excitability in this area [79]. A neuroprotective role has been attributed to apelin, as it has been shown that it attenuates neuron apoptosis after ischaemia/reperfusion injury [80].…”
Section: Ace2 In the Brainmentioning
confidence: 99%
“…More recently, however, it has been shown that microinjection of apelin-13 into the subfornical organ, which detects circulating signalling molecules, decreases BP and HR (Dai et al 2013). Additionally, the apelinergic system has an important role in cardiac function.…”
Section: Cardiovascular Roles Of Apelin/apjmentioning
confidence: 99%